Influence of prior microstructure on the mechanical and microstructural properties of C–Mn–B steel after spheroidizing annealing. (21st October 2021) - Rivolta, B.; Gerosa, R.; Sala, C.; Tavasci, F.; Angelini, L.; Bolognani, N.; Panzeri, A.; Parimbelli, A.
ABSTRACT: During spheroidizing annealing of steels, the carbide shape is modified from lamellar to spheroidal for increasing cold deformability. The aim of this work is to study the kinetics and the mechanical properties of a C–Mn–B steel grade after spheroidizing annealing, varying the prior microstructure produced by industrial conventional and thermo-mechanical hot rolling with different Stelmor cooling rates. Moreover, different prior microstructures were also produced by laboratory heat treatments. Microstructural analysis, hardness tests, and tensile tests were carried out at different soaking times. The results show that a better distribution of the carbon in the metal matrix obtained in bainitic and martensitic microstructures results in a more uniform dispersion of the carbides with higher mechanical resistance and deformability. The ferritic and pearlitic microstructures obtained by thermo-mechanical hot rolling are able to produce more homogeneous carbides when compared with the traditional hot rolling.